FUNDAMENTALISME AGAMA - Nur Rosidah (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2012)
Al-Qur’an frequently stated as a basic source for violence and terror as well as Islamic fundamentalism. This is because materially there are some provocative-agitative verses in al-Qur’an for violence doer and terrorist. This article discussed about the way to study Qur’an verses on violence and the interpretation methodology applied to understanding that verses.